Germline and somatic mutations in histologically atypical congenital hyperinsulinism - Larsen, Annette Rønholt; Globa, Evgenia; Andersen, Ditte Caroline; Limbert, Catarina; Mattsson, Åsa Löfgren; Nielsen, Anne Lerberg; Mortensen, Michael Bau; Hejbøl, Eva Kildall; Brusgaard, Klaus; Detlefsen, Sönke; Christesen, Henrik Thybo (Frontiers in Endocrinology, 2026)
BackgroundIn histologically atypical congenital hyperinsulinism (CHI), correlations between clinical, histological and genetic features are largely unknown. Laser-capture microdissection may be used to identify low-grade mosaic DNA variants in the islets of Langerhans.AimTo investigate genotype-histotype-phenotype correlations histologically in atypical CHI.MethodsIn our single-center cohort of hyperinsulinemic hypoglycemia (HH) patients, 77 underwent pancreatic surgery. In those with histologically atypical CHI, genetic analyses included sequencing of frequent CHI genes from blood and bulk pancreatic tissue and tests for Beckwith-Wiedemann Syndrome (BWS) where appropriate. If negative, a targeted 140-gene panel including the non-coding region of HK1 was performed in blood, pancreatic bulk tissue and islets isolated by laser-capture microdissection. Histological, immunohistochemical and morphometric analyses were performed on pancreatic tissue.ResultsThe 77 HH patients were classified histologically as KATP-channel focal CHI (n=48), KATP-channel diffuse CHI (n=14), insulinoma (n=6), non-insulinoma HH in teenagers (n=1), BWS (n=1), unclassified (n=2). Histologically atypical CHI patients (n=5/70; 7.1%) had a median (range) birth weight of 2965 (2650-3385) grams and a clinical disease onset at 93 (1-259) days. 18F-DOPA PET/CT showed diffuse tracer uptake. In three patients, genetic analysis showed HK1 intron 2 variants, of which one was present in germline (de novo heterozygous) while the other two had somatic low-grade mosaic alterations in bulk pancreatic tissue (n=1) or exclusively in islets after isolation by laser-capture microdissection (n=1). Patient 4 showed a CACNA1D frameshift mutation suggesting Cav1.3-channel gain-of-function properties. No relevant genetic changes were found in Patient 5. In all five atypical CHI specimens, pancreatic histology showed slight changes with areas having pronounced occurrence of large islets of Langerhans, while small islets and endocrine cell clusters were evenly distributed. Giant cell nuclei were observed, but at much lower frequencies compared to KATP-channel diffuse CHI.ConclusionHistologically atypical CHI was seen in 7.1% of surgically treated CHI patients and characterized by discrete changes with enlarged islets of Langerhans and a low frequency of giant nuclei in endocrine cells. Genetics showed heterozygous or low-grade mosaic HK1 intron 2 DNA variants in three patients. Low-grade mosaic pancreatic genetic changes may only be detectable after islet isolation by laser-capture microdissection.